Should I speak up? How trust in leaders and leader-leader exchanges influence nurses' voice behaviour - Kang‐I. Chao; Jen‐Wei Cheng; Hung‐Chieh Yen; Shih‐Hao Lu (Wiley, 2024)
Abstract Aim Discussing the nurses' voice behaviour could support the managers in making the right decisions and solve problems. Design This was a discursive paper. Methods The discursive was based on reviewing the literature. Results Nurses play a critical role in offering useful constructive advice, which leads to management figuring out and solving problems immediately for the purpose of bettering the working environment. Therefore, we assert that trust in leadership and the leader-leader exchange system also plays a critical role in enforcing voice behaviour. Trust is a crucial aspect of voice behaviour, and integrated trust in leadership and leader-leader exchange as a possible practical suggestion for the fostering of voice behaviour are proposed. Nurse managers must maintain a sense of reciprocal moral obligation in order to nurture value‐driven voice behaviour. It is important that open dialogue, active listening and trust in leadership exist. Nurse managers must consider ways to foster mutual trust, and support and enable nurses to use voice behaviour in everyday practice.